MonoSeq Variant Caller Reveals Novel Mononucleotide Run Indel Mutations in Tumors with Defective DNA Mismatch Repair. Issue 10 (8th August 2016) - Walker, Christopher J.; Miranda, Mario A.; O'Hern, Matthew J.; Blachly, James S.; Moyer, Cassandra L.; Ivanovich, Jennifer; Kroll, Karl W.; Eisfeld, Ann‐Kathrin; Sapp, Caroline E.; Mutch, David G.; Cohn, David E.; Bundschuh, Ralf; et al.
Abstract : MonoSeq was designed to filter noise associated with sequencing low complexity DNA and improve variant detection in repeat regions. Using Sanger sequencing as a reference, we showed MonoSeq has greater reliability than VarScan for detection of subclonal variants in mononucleotides. MonoSeq analysis of 540 primary endometrial cancers revealed a novel hotspot indel in an A7 repeat the terminal exon of ARID5B . ABSTRACT: Next‐generation sequencing has revolutionized cancer genetics, but accurately detecting mutations in repetitive DNA sequences, especially mononucleotide runs, remains a challenge. This is a particular concern for tumors with defective mismatch repair (MMR) that accumulate strand‐slippage mutations. We developed MonoSeq to improve indel mutation detection in mononucleotide runs, and used MonoSeq to investigate strand‐slippage mutations in endometrial cancers, a tumor type that has frequent loss of MMR. We performed extensive Sanger sequencing to validate both clonal and subclonal MonoSeq mutation calls. Eighty‐one regions containing mononucleotide runs were sequenced in 540 primary endometrial cancers (223 with defective MMR). Our analyses revealed that the overall mutation rate in MMR‐deficient tumors was 20–30‐fold higher than in MMR‐normal tumors. MonoSeq analysis identified several previously unreported mutations, including a novel hotspot in an A7 run in the terminal exon of ARID5B .The ARID5B indel mutations were seen in both MMR‐deficient and MMR‐normal tumors, suggesting biologic selection. The analysis of tumor mRNAs revealed the presence of mutant transcripts that could result in translation of neopeptides. Improved detection of mononucleotide run strand‐slippage mutations has clear implications for comprehensive mutation detection in tumors with defective MMR. Indel frameshift mutations and the resultant antigenic peptides could help guide immunotherapy strategies.